UMPSA advances bilateral ties with Universitas Islam Riau - Nur Ezzati, Mohd Nasir (UMPSA, 2025)
PEKAN, 21 February 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has officially strengthened its partnership with Universitas Islam Riau (UIR) through the signing of a Memorandum of Understanding (MoU).